Home Sweet Home? Housing Activism and Political Commemoration in Sixties Ireland. (25th February 2019) - McEneaney, Sinead
Abstract: This paper examines the explosion of activism around housing in Ireland in the late Sixties. At a time of political commemoration around the anniversaries of the 1916 Rising, and the establishment of the first revolutionary independent parliament (Dáil) in 1919, a group of activists calling themselves the Dublin Housing Action Committee sought to disrupt political consensus and ask serious questions about the priorities of the Irish state. The group began through co-operation between homeless people in the city, but soon garnered support from anti-establishment agitators within the republican party, Sinn Féin. By 1969, the group was pressing government for response to the acute housing crisis in the city.